Ilmu politik Islam - H. Zainal Abidin Ahmad (Bulan Bintang, 1977)
Oen, Jil. I=c.1-2; Jil. II=c.1-6; Jil. III=c.1-9;Jil.IV=C.1-4; Jil.V=c.1/oen, jil. 4=c.5/AST JIL.4 =C.6/tr, jil.3=c.10; jil.5=c.2/oen, jil.5=c.3/tr, jil.1=c.3/tr, jil.2=c.7/tr, jil.5=c.4/ast jil.1 =c.4,jil2 =c.8,jil.3 =c.11,jil.4 =c.7/tr, jil.3=c.12; jil.5=c.5